2013
DOI: 10.1007/s00213-013-3046-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute escitalopram treatment inhibits REM sleep rebound and activation of MCH-expressing neurons in the lateral hypothalamus after long term selective REM sleep deprivation

Abstract: Rationale Selective rapid eye movement sleep (REMS) deprivation using the platform-on-water ("flower pot") method causes sleep rebound with increased REMS, decreased REMS latency, and activation of the melaninconcentrating hormone (MCH) expressing neurons in the hypothalamus. MCH is implicated in the pathomechanism of depression regarding its influence on mood, feeding behavior, and REMS. Objectives We investigated the effects of the most selective serotonin reuptake inhibitor escitalopram on sleep rebound fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 54 publications
2
7
0
Order By: Relevance
“…Based on the aggregate sleep measures (Table 3 ), we did not find any changes denoting enhanced wake pressure or sleep fragmentation after RD, which is consistent with previous reports [ 11 , 12 , 76 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Based on the aggregate sleep measures (Table 3 ), we did not find any changes denoting enhanced wake pressure or sleep fragmentation after RD, which is consistent with previous reports [ 11 , 12 , 76 ].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, stress could be a main factor also in the suppression of NREM sleep [ 58 60 ]. Some studies have revealed also an enhancement in REM episode duration (in the first 3 h [ 12 ] and 2–24 h of the recovery period after 72 h RD [ 11 ]; in the first 6 h after 2 days of 18 h RD [ 56 ]). However, we did not find here an enhanced REM duration after RD; in fact, there was a tendency to decrease regarding this parameter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, escitalopram has the ability to diminish the activation of hypothalamic neurons containing melanin concentrating hormone (MCH) and to suppress REM sleep rebound [30]. The potential interplay between SPX and MCH signalling is so far unknown, however it is worth noting that escitalopram may inhibit the action of another regulatory neuropeptide in the hypothalamus.…”
mentioning
confidence: 99%